2006
DOI: 10.2174/092986606776819501
|View full text |Cite
|
Sign up to set email alerts
|

Structure Formation in Short Designed Peptides Probed by Proteolytic Cleavage

Abstract: The formation of local structure, in short peptides has been probed by examining cleavage patterns and rates of proteolysis of designed sequences with a high tendency to form beta-hairpin structures. Three model sequences which bear fluorescence donor and acceptor groups have been investigated: [see text]. Fluorescence resonance energy transfer (FRET) provides a convenient probe for peptide cleavage. MALDI mass spectrometry has been used to probe sites of cleavage and CD spectroscopy to access the overall back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The use of D-Pro also hindered the degradation of the peptides by proteinase K, subtilisin, elastase, and collagenase. 4 Another example of the use of unnatural amino acids in peptides is the incorporation of b-and c-amino acids in place of a-amino acids. The Seebach lab has found that peptides containing all b-and all c-amino acids were stable to 15 different peptidases in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of D-Pro also hindered the degradation of the peptides by proteinase K, subtilisin, elastase, and collagenase. 4 Another example of the use of unnatural amino acids in peptides is the incorporation of b-and c-amino acids in place of a-amino acids. The Seebach lab has found that peptides containing all b-and all c-amino acids were stable to 15 different peptidases in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in this field have used FRET based assays both in vivo and in vitro to study structure and stability of small peptides. 4,8 However, the attachment of large proteins to either end of the b-hairpin may influence the enzymatic cleavage, particularly with exopeptidases. Thus, we have used HPLC based experiments that remove the need for bulky GFP-derived fluorophores that may interfere with the enzyme binding and function.…”
Section: Introductionmentioning
confidence: 99%
“…We have earlier reported the design of a protease substrate containing cleavage sites for diverse proteases, which can be used to analyze protease profiles in Plasmodium falciparum. 19 Proteolysis of internally quenched fluorescent peptides can also provide a probe for structure formation in designed sequences 20. In this report, we describe a designed collagenase substrate which contains as many as three internal Gly‐Pro‐X segments and demonstrate specific cleavage by Clostridium histolyticum collagenase.…”
Section: Introductionmentioning
confidence: 95%
“…A peptide having the amino acid sequence Ac-RWVKVNGOWIKQ-NH 2 (here-in referred to as “WKWK”) has proven to be highly resistant to degradation by trypsin, α-chymotrypsin and Pronase E compared to a scrambled peptide control [14]. In comparison to WKWK, a related peptide Ac-RWVKVpGKWIKQ-NH 2 (WKpG) having D-Pro-Gly (pG) in place of Asn-Gly (NG) shows enhanced folding by increasing the cross-strand interactions and thus further stabilizing the β-hairpin [14, 19]. The WKpG peptide has also been demonstrated to confer greater resistance than WKWK to enzymatic cleavage by trypsin, proteinase K, subtilisin, elastase, and collagenase [14, 19].…”
Section: Introductionmentioning
confidence: 99%